Expression of a soluble and functional form of the human beta 2 integrin CD11b/CD18. - Dana, N (1991)
Polymorphonuclear cells and monocytes (phagocytes) are a critical component of host defense against infections. However, these cells also play a significant role in host tissue damage in many noninfectious diseases, such as ischemia-reperfusion injury syndromes and rejection of transplanted organs. The leukocyte adhesion molecule family CD11/CD18 (beta 2 integrins) is critical to the function of polymorphonuclear cells and monocytes in inflammation and injury. Inherited deficiency of CD11/CD18 impairs phagocyte chemotaxis, adhesion and transmigration across endothelium, and clearance of invading microorganisms through phagocytosis and cell-mediated killing. Furthermore, murine monoclonal antibodies directed against the CD11b/CD18 (CR3) heterodimer have been shown to reduce, by 50%-80%, phagocyte-mediated ischemia-reperfusion injury in several organ systems, such as the myocardium, liver, and gastrointestinal tract and to inhibit development of insulin-dependent diabetes mellitus in nonobese diabetic (NOD) mice. Expression of CD11b/CD18 in a soluble and functional form might therefore be potentially useful as an anti-inflammatory agent. We have now expressed a recombinant soluble heterodimeric form of this human beta 2 integrin, normally expressed as two noncovalently associated membrane-bound subunits. The secreted receptor exhibited direct and specific binding to its ligand, iC3b, the major complement C3 opsonin, and inhibited binding of polymorphonuclear cells to recombinant interleukin 1-activated endothelium.